2020
DOI: 10.1021/acssuschemeng.0c07232
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of Gas Phase Sugar Cracking to Glycolaldehyde and Other Oxygenates

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…Figure depicts these reaction routes starting with opening of the cyclic hemiacetal form of erythrose. This is followed by a consecutive reaction based on the surface species measured here and elsewhere (glycolaldehyde). , The complexity of this reaction network illustrates that the catalyst design for any of these reactions would require a systematic approach to assure that a desired product can be obtained with high selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Figure depicts these reaction routes starting with opening of the cyclic hemiacetal form of erythrose. This is followed by a consecutive reaction based on the surface species measured here and elsewhere (glycolaldehyde). , The complexity of this reaction network illustrates that the catalyst design for any of these reactions would require a systematic approach to assure that a desired product can be obtained with high selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…2.1 | Sugar, starchy, and lignocellulosic feedstocks A set of 21 scenarios was defined, considering different feedstocks produced in different countries and considering different uses of biomass residues (by-products) from the feedstock production (Table 1). Selection of regions was based on information retrieved from the Danish chemical industry, which needs to decide where to source sugar feedstocks for bio-based chemicals (Schandel et al, 2021). The sugar feedstocks sugar beet and sugar cane represent, respectively, 20% and 80% of the world's sugar production globally (~180 million tons produced in 2021; USDA, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…One biochemical of particular interest to the chemical industry is bio-based monoethylene glycol (MEG), which can be used in the production of polyester fibers and film and for polyethylene terephthalate (PET) resins (Rosenboom et al, 2022;Spekreijse et al, 2019). Sugars can be converted to bio-based MEG by cracking (hydrous pyrolysis) to glycolaldehyde intermediate, followed by its catalytic hydrogenation to the final MEG product (Schandel et al, 2021). Recent life cycle assessment (LCA) studies showed that environmental performance of sugars extracted from first-generation feedstocks (i.e., sugar and starchy crops) might be comparable with that of sugars extracted from second-generation feedstocks (i.e., lignocellulosic biomass; Dammer et al, 2017Dammer et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…fine glass beads, inside a fluidized-bed reactor, altered the product distribution significantly and substantially improved the GA selectivity to 50-80%. 19,20 This hydrous pyrolysis process is also called 'sugar cracking' in which the glucose thermally decomposes into mainly GA along with other small oxygenates at 500 to 550 °C with gas residence times of 1 to 2 s. 5 The thermal decomposition chemistry is complex, and the process is strongly affected by operating conditions such as temperature, glucose concentration, residence time, etc. [19][20][21] Specifically, the heating rate has been acknowledged as an important parameter, where e.g.…”
Section: Introductionmentioning
confidence: 99%